Identification and characterisation of flotillin-2 as a molecular target in breast and bladder cancers - Jafarzadeh, Narges (2013)
Invasive breast and bladder cancers are associated with poor clinical outcome and are characterised by a genotype that is distinct from superficial disease. Predicting the invasive and metastatic potential of tumours at the time of diagnosis remains a major challenge in cancer management. Exploiting a multi-component data-mining in silicostrategy, genes associated with an invasive phenotype were targeted. These bioinformatics screens were conducted on previously published and publicly available datasets derived from various high-throughput genome-wide experimental data based on gene expression arrays and array-based comparative genomic hybridisation. Differentially expressed genes between high and low-risk cancers were functionally annotated by gene ontology and compared to available expression datasets. Overexpression of a lipid raft associated protein, Flotillin 2 (FLOT2) in invasive cancers was identified. The FLOT2 locus (17q11-q12) was associated with copy number gains in 15% of tumours.Flotillin-2 is an important lipid raft marker and is predicted to be involved in cell-matrix adhesion, cell migration and signal transduction. Immunohistochemistry was used to evaluate flot2 expression and localisation in formalin fixed paraffin-embedded malignant and non-malignant breast cancers. Flot2 localisation varied from a cytoplasmic distribution in normal cells to a more cell-cell contact distribution in malignant cells. A correlation was found between flot2 overexpression in the invasive compartments of tumour tissues and clinical stage. The staining intensity in the invasive compartment increased with cancer progression. Flot2 protein expression was tested in an independent bladder cancer tissue microarray series by immunohistochemistry. Flot2 protein expression increased with bladder cancer progression as well. Subsequently, FLOT2was knockdown in bladder and breast cancer cells in vitro by siRNA. Migration and invasion assays were employed to determine the phenotypic effects of FLOT2 inhibition. The inhibition ofFLOT2 expression in knockdown cells was confirmed by RT-qPCR and Western blotting. Knockdown of FLOT2 led to a significant reduction in the invasive and migtransduction. Immunohistochemistry was used to evaluate flot2 expression and localisation in formalin fixed paraffin-embedded malignant and non-malignant breast cancers. Flot2 localisation varied from a cytoplasmic distribution in normal cells to a more cell-cell contact distribution in malignant cells. A correlation was found between flot2 overexpression in the invasive compartments of tumour tissues and clinical stage. The staining intensity in the invasive compartment increased with cancer progression. Flot2 protein expression was tested in an independent bladder cancer tissue microarray series by immunohistochemistry. Flot2 protein expression increased with bladder cancer progression as well. Subsequently, FLOT2was knockdown in bladder and breast cancer cells in vitro by siRNA. Migration and invasion assays were employed to determine the phenotypic effects of FLOT2 inhibition. The inhibition ofFLOT2 expression in knockdown cells was confirmed by RT-qPCR and Western blotting. Knockdown of FLOT2 led to a significant reduction in the invasive and migratory cellular phenotypes. The precise mode of action of flot2 remains to be elucidated but it is predicted to play an important role intransmembrane signal transduction, cell adhesion and endocytosis. Incidentally,FLOT2 overexpression has also been shown to enhance the spreading of cells, formation of filopodia as well as melanoma progression and metastasis. This study identifies and confirms flot2 overexpression as a common feature of invasive breast and bladder cancers.In addition, the functional targeting experiments and genedosage dependent FLOT2 overexpression in invasive breast and bladder cancers confirm a link between FLOT2 and a pro-invasive cancer phenotype. flot2 remains to be elucidated but it is predicted to play an important role intransmembrane signal transduction, cell adhesion and endocytosis. Incidentally, FLOT2 overexpression has also been shown to enhance the spreading of cells,formation of filopodia as well as melanoma progression and metastasis. This study identifies and confirms flot2 overexpression as a common feature of invasive breast and bladder cancers.In addition, the functional targeting experiments and genedosage dependent FLOT2 overexpression in invasive breast and bladder cancers confirm a link between FLOT2 and a pro-invasive cancer phenotype.